Comparison of titer results obtained using immediate spin one‐dilution techniques to a reference method. (13th April 2019) - Yazer, Mark H.; Dunbar, Nancy M.; Bub, Carolina Bonet; Condict, Brittany E.; Dunn, Robyn; Janoušková, Miloslava; Kutner, Jose; Landová, Ludmila; Lejdarová, Hana; Nesvačilová, Božena; Pacasová, Rita; Procházková, Renata; et al.
Abstract : BACKGROUND: Many transfusion services determine the titer of potentially incompatible plasma‐containing products by performing a one‐dilution titer at their selected titer threshold. This study compared the results of immediate spin (IS) one‐dilution titers determined by three methods with a reference standard method. METHODS: Plasma‐containing products from group A and O donors were titered using the participant's routine IS one‐dilution titer method. No time or temperature incubations were performed, and antihuman globulin reagent was not used. The samples were then tested using a reference method, which was a saline tube test with a 1‐hour room temperature incubation; antihuman globulin was not used in the reference method. The results of the one‐dilution titer were then compared to that obtained in the reference method. RESULTS: Nine centers participated in this study. There were 698 antibodies from 374 units tested by the manual IS tube one‐dilution titer method; sensitivity was 0.88 (95% confidence interval [CI], 0.83–0.92), and specificity was 1.00 (95% CI, 0.98–1.00). There were 412 antibodies from 206 units tested by the manual and automated IS buffered gel card one‐dilution titer method; sensitivity was 0.95 (95% CI, 0.91–0.98), and specificity was 0.87 (95% CI, 0.81–0.91). There were 98 antibodies from 49 units tested by an automated microplate IS one‐dilution titer method; sensitivity was 0.76 (95% CI, 0.71–0.93), and specificity was 0.96 (95% CI, 0.92–0.99). All three methods had an accuracy rate of 90% or greater. CONCLUSION: The manual and automated one‐dilution titer methods are suitable for screening plasma‐containing units, although more evaluation of the automated microplate method might be required.